Analysis of Fixed Asset Borrowing Management at UPTD RSJ Prof. Dr. V. L. Ratumbuysang - Manuputty, Semuel Isack Yoseph; Kalangi, Lintje; Datu, Christian (Formosa Journal of Applied Sciences, 2024)
Management of regional property plays a significant role in assisting the government to optimize the performance and procedures related to regional property management. This research was conducted to analyze whether the borrowing and utilization of fixed assets at UPTD RSJ Prof. Dr. V. L. Ratumbuysang adhere to the regulations stipulated in Minister of Home Affairs Regulation Number 19 of 2016. Utilizing a qualitative approach with a descriptive case study analysis method, this research delves into the procedures implemented for borrowing and utilizing fixed assets. The findings reveal that the execution of these procedures has not fully aligned with the regulations. Notably, the asset manager did not prepare a Handover Minutes (Berita Acara Serah Terima or BAST) during the loan utilization process.